Gambaran Pengetahuan Remaja tentang Infeksi Menular Seksual (IMS) di SMAN 1 Mandirancan Kelas XI MIPA - Erawati, Heni; Novianty, Atiek (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Sexually transmitted infections (STIs) are infections that are transmitted mainly through sexual intercourse. Indonesia's 2020 health profile reported that STIs such as HIV are increasing every year. The prevalence of STIs in Indonesia in indonesia was 11,133 cases. The prevalence of syphilis was 3,868 cases, gonorrhea 2,486 cases, and HIV/AIDS 9,327 cases. The purpose of this study was to determine the knowledge of adolescents about sexually transmitted infections (STIs) at Senior High School 1 Mandirancan Class XI MIPA. This study used descriptive research design. With a population of 216 students and a sample of 68 respondents taken by random sampling. The research was conducted at Senior High School 1 Mandiracan in April-June 2024. By using research instruments in the form of questionnaires, this study used primary and secondary data, the analysis in this study used univariate analysis with frequency distribution. The results of this study obtained the results of adolescent knowledge about STIs as many as 50 students (73.5%) were well informed and 28 students (26.5%) were moderately knowledgeable. Adolescents knowledge about sexually transmitted infections at Senior High School 1 Mandirancan Class XI MIPA has good knowledge category. It is expected that the school will collaborate with health workers to conduct socialization about STIs and conduct counseling to students about STIs.